Biomarkers of erythropoiesis response to intravenous iron in a crossover pilot study in unexplained anemia of the elderly. Issue 1 (31st December 2023) - Yoo, Justin J.; Cohen, Harvey J.; Artz, Andrew S.; Price, Elizabeth; Fill, Jeffrey A.; Prchal, Josef; Sapp, Shelly; Barnhart, Huiman
ABSTRACT: Anemia is common in older adults, but often unexplained. Previously, we conducted a randomized, controlled trial of intravenous (IV) iron sucrose to study its impact on the 6-minute walk test and hemoglobin in older adults with unexplained anemia and ferritin levels of 20–200 ng/mL. In this report, we present for the first time the response of hemoglobin, as well as the dynamic response of biomarkers of erythropoiesis and iron indices, in a pooled analysis of the initially IV iron-treated group of 9 subjects and the subsequently IV iron treated 10 subjects from the delayed treatment group. We hypothesized that there would be a reproducible hemoglobin response from IV iron, and that iron indices and erythropoietic markers would reflect appropriate iron loading and reduced erythropoietic stress. To investigate the biochemical response of anemia to IV iron, we studied the dynamics of soluble transferrin receptor (STfR), hepcidin, erythropoietin (EPO), and iron indices over 12 weeks after treatment. In total, all 19 treated subjects were evaluable: 9 from initial treatment and 10 after cross-over. Hemoglobin rose from 11.0 to 11.7 g/dL, 12 weeks after initiating IV iron treatment of 1000 mg divided weekly over 5 weeks. We found early changes of iron loading after 1–2 IV iron dose: serum iron increased by 184 mcg/dL from a baseline of 66 mcg/dL, ferritin by 184 ng/mL from 68 ng/mL, and hepcidin by 7.49 ng/mL from 19.2 ng/mL, while STfR and serum EPO declined by 0.55 mg/L and 3.5 mU/mL from 19.2 ng/mL and 14 mU/mL, respectively. The erythroid response and evidence of enhanced iron trafficking are consistent with the hypothesis that IV iron overcomes iron deficient or iron-restricted erythropoiesis. These data provide new insight that iron-restricted erythropoiesis is a potential and targetable mechanism for patients diagnosed with unexplained anemia of the elderly and offers support for larger prospective trials of IV iron among anemic older adults of low to normal ferritin.